2015
DOI: 10.1007/s40746-015-0021-9
|View full text |Cite
|
Sign up to set email alerts
|

Anaemia in the Premature Infant and Red Blood Cell Transfusion: New Approaches to an Age-Old Problem

Abstract: Opinion statementRed blood cell (RBC) transfusion is a common intervention in very preterm infants with variable utilisation between centres and individual clinicians. This variation likely reflects uncertainty about who, when and how much to transfuse. Most RBC transfusions are given in small volumes as "top-up" for anaemia or cumulative phlebotomy loss. Whilst the newly born infant may have a low haemoglobin (Hb) value, it is uncertain if this is of clinical or physiologic significance except at extreme valu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
16
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(16 citation statements)
references
References 51 publications
0
16
0
Order By: Relevance
“…However, normative values for reticulocyte counts in preterm infants remain largely unknown and warrant further investigation. In Australasia, the lack of clarity about when to transfuse these infants adds urgency to the need for research into newer clinical adjuncts, such as the degree of tissue hypoxia detected by NIRS to determine timing and efficacy of transfusion for AOP …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, normative values for reticulocyte counts in preterm infants remain largely unknown and warrant further investigation. In Australasia, the lack of clarity about when to transfuse these infants adds urgency to the need for research into newer clinical adjuncts, such as the degree of tissue hypoxia detected by NIRS to determine timing and efficacy of transfusion for AOP …”
Section: Discussionmentioning
confidence: 99%
“…More recently, researchers have examined the clinical utility of the regional tissue oxygenation (rSO 2 ), measured non‐invasively by near‐infrared spectroscopy (NIRS), as an indicator of anaemia‐induced tissue hypoxia . As a mixed arteriolar, capillary and venular oxygenation index, rSO 2 may inform adequacy or otherwise of oxygen delivery relative to consumption at the tissue level.…”
mentioning
confidence: 99%
“…The 2 hypothetical scenarios in Table highlight the limitation of Hb as a proxy for oxygen delivery (DO 2 , ml/kg/min). Furthermore, ‘adequacy’ of DO 2 must be considered in the context of oxygen consumption (VO 2 ) in a given infant at any given moment in time (Andersen et al , ). Crucially, in pre‐term infants, rates of oxygen consumption are dynamic and influenced by many factors, including post‐natal age, body temperature, pulmonary work of breathing and inflammatory process (e.g.…”
Section: When Do We Give Rbc Transfusions For Anaemia Of Prematurity?mentioning
confidence: 99%
“…Regional oxygenation (rSO 2 ) by near-infrared spectroscopy (NIRS) has the potential to inform vital organ oxygenation and has been advocated as a potential clinical adjunct to the current haemoglobin-based neonatal transfusion guidelines (1). Researchers have demonstrated that transfusion of red blood cells (RBCs) for anaemia of prematurity leads to increases in rSO 2 and/or decreases in fractional tissue oxygen extraction (FTOE) in the brain, kidney, gut and muscle up to 24 hours after transfusion (2)(3)(4).…”
Section: Introductionmentioning
confidence: 99%